Why Do Adolescents Use Social Media? Validation of the Croatian version of Motives to Use Social Networking Sites Scale - Martinac Dorčić, Tamara; Mohorić, Tamara; Kukić, Miljana (European Journal of Mental Health, 2025)
Introduction: Motivation for social media use is a multidimensional construct; however, most existing questionnaires focus solely on motives and do not distinguish between active and passive use. To address this, the Motives to Use Social Networking Sites Scale (MOTUS; Reimann et al., 2023) was developed, integrating motivational aspects and usage modes. Aim: This study examined the construct and convergent validity of the MOTUS scale in Croatian high school students. The original eight-factor model was tested with confirmatory factor analysis (CFA), and measurement invariance across gender was assessed with multigroup CFA. Associations with social media, loneliness, and fear of missing out were analysed for convergent validity. The Average Variance Extracted (AVE) and the Heterotrait– Monotrait (HTMT) ratio were also calculated to further evaluate the MOTUS scale. Reliability was assessed with Cronbach’s α and Macdonald’s ω. Methods: Participants were 853 adolescents aged 14–19 (M = 16.21, SD = 1.07; 69.6% women). In addition to MOTUS, they completed the Fear of Missing Out Scale (FoMO), De Jong Gierveld Loneliness Scale and estimated daily time on social media. Results: The eight-factor model showed acceptable fit after removing one item with cross-loadings (CFI = .916, TLI = .900, RMSEA = .061, SRMR = .074). Measurement invariance supported configural, metric, and scalar equivalence across gender. Convergent validity was confirmed through significant correlations between MOTUS subscales, time on social media, and FoMO. Conclusions: The MOTUS scale shows acceptable psychometric properties for assessing motives and usage modes of social media in Croatian adolescents.